Efektivitas Promosi Kesehatan Terhadap Pengetahuan Tentang Deteksi Dini Kanker Serviks - Dhiajeng Anisa Vera; Fitria Melina (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Cancer is one of the main causes of cervical cancer deaths and deaths by 10,3%. The prevalence of tumors or cancer in Indonesia is 1,8 per 1000 population, the province of DIY has the highest prevalence for cancer of 4,9%. In 2017 the lowest coverage rates for early detection of cervical cancer were in Bantul Regency (9,03%), and the incidence of cervical cancer with guidelines for the highest coverage data for early detection of cervical cancer was in the Sanden sub-district (7,23%). One method for disseminating information about early detection of cervical cancer is to do health promotion. To know the effectivness oh health promotion on mothers knowedge about early detection of cervical cancer in Dusun Daleman Kelurahan Gadingharjo Sanden Bantul. The type of research is quantitative with the Pre-Experimental One Group Pretest-Posttes Design method. The population are 57, the sample are 53 respondents and taken by Total Sampling technique. The knowledge of mothers before they were given health promotion was conducted, only 58,5%, showed minus knowledge. After given the health promotion was conducted 73,6%, showed enough knowledge. The result of Wilcoxon Test with confidence level α = 0,05, result in signifikan 0,000. Health promotion with an effective lecture method to increase maternal knowledge about early detection of cervical cancer in Dusun Daleman Kelurahan Gadingharjo Sanden Bantul.